Analisis Penyelesaian Dana Macet di Koperasi Konsumen Guru dan Pegawai Negeri di Medan Area: Analysis of Settlement of Bad Funds in Teacher and Civil Servant Consumer Cooperatives in the Medan Area - Perkasa, Ripho Delzy; Wulandari Prabowo, Indah Cahyaning; Siregar, Naiya Syahfitri (Absorbent Mind, 2024)
The “Consumer of Teachers and Civil Servants” cooperative in developing its business has helped economic institutions that can improve the welfare of teachers and civil servants. However, the implementation of the “Consumer Teachers and Civil Servants” cooperative does not always run smoothly but can also result in problems in the cooperative such as the occurrence of bad funds which can be detrimental to the cooperative and cooperative employees. Therefore, this research aims to (1) Find out the causes of the problems faced by the “Consumer Teachers and Civil Servant” cooperative, (2) Identify solutions to these problems. The type of research method used is descriptive research, with qualitative analysis techniques proposed by Sugiyono through interviews, observation, and documentation. The research subjects are (1) Chairman of the Board (2) IT Expert (3) Administrative Executive of the “Consumer Teachers and Civil Servants” cooperative located on Jl.A.R. Hakim No. 177 A Medan Area. The results of this research show that the factors causing the occurrence of non-performing funds in the “Consumer Teachers and Civil Servants” cooperative are: (1) There is no limit for borrowing and no due date for repaying the loan (2) Lack of supervision and firmness on the part of the cooperative (3) Cooperative members borrow funds to the cooperative then borrow from the bank (4) Members have an accident or disaster. Alternative solutions to problems with non-performing funds include: (1) approaching members, (2) rescheduling, (3) reconditioning, (4) extending time.